Shadow puppet, Gamelan, Malangan TAXONOMY OF THE GENDING OF THE FILM IN THE CASE OF NICK O'NEILL, NICK O'NEILL : Taksonomi Gending Wayang Kulit Gaya Malangan Dalam Pementasan Dalang Ki Niko Anom Carito - Mohammad Febian Pratama; Rizki Agung Novarianto Novariyanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to examine the taxonomy of gending wayang kulit gaya Malangan in the performances of the puppeteer Ki Niko Anom Carito. This study also employs a qualitative approach with a focus on art taxonomy, identifying and classifying the gending used in the performances, as well as understanding the symbolic meanings of the gending and their functions in creating the atmosphere of wayang kulit gaya Malangan performances. The results indicate that puppeteer Ki Niko Anom Carito preserves traditional gending such as Eling-Eling Malangan, Gandakusuma, and Samirah, each of which holds its own philosophical and spiritual values. Additionally, the wayang kulit gaya Malangan performances by Ki Niko Anom Carito rely on the structure of pathet and ayak-ayak as characteristic musical features of the East Javanese wayang kulit, with the addition of pathet sepuluh introducing various innovations that make wayang kulit gaya Malangan distinct from other East Javanese styles. This research demonstrates how wayang kulit gaya Malangan performances serve not only as entertainment but also as a means of preserving local culture and showcasing the identity of the Malang community.